Synthesis and characterization of a photocatalytic material from TiO2 nanoparticles supported on zeolite obtained from ignimbrite residue used in decolorization of methyl orange - Huayna Gaona, Gianina Elizabeth (2024)
In the present work, a TiO2/zeolite photocatalyst was synthesized by dispersing TiO2 nanoparticles obtained through the sol-gel method onto the surface of natural zeolite derived from ignimbrite residue. The zeolite was obtained from an ignimbrite rubble treatment collected from a quarry in Arequipa City, Peru. The research focused on the effect of zeolite on the TiO2 nanoparticles. The synthesized photocatalysts were characterized using various techniques, including field-emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray (EDS), X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS), and Brunauer–Emmett–Teller surface area analysis (BET). The results revealed that the TiO2/zeolite samples displayed high crystallinity, with TiO2 being present in three phases and zeolite being present in the analcime phase. Furthermore, these samples exhibited a band gap of 3.14 eV and a high surface area compared to that of bare TiO2. Finally, the photocatalytic activity of the TiO2/zeolite composite obtained was evaluated toward the decomposition of 10 ppm and 20 ppm of methyl orange (MO) dye. The TiO2/zeolite samples demonstrated improved photocatalytic activity compared to that of pristine TiO2 under the same experimental conditions. This enhancement is primarily attributed to the increased specific surface area of the TiO2/zeolite samples, making them promising materials for future efficient and sustainable photocatalytic applications.